Polygamy and Wife's Rights in Polygamy - Samsul Fajeri (Ad-dawl : Jurnal Islamic Studies, 2025)
This research aims to analyze the legal regulations regarding polygamy and the protection of wives' rights in polygamous marriages, both in positive law and in Islamic law. This research uses a library research method with a normative juridical approach. normative juridical approach. Data were collected through document studies of relevant legal literature, books, journals, and official documents. Data analysis was conducted using the content analysis method, with stages of source identification, analysis based on Islamic law theory and positive law, and preparation of descriptive-analytical analysis to obtain a comprehensive conclusion. The results show that in the practice of polygamy there is a dualism of legal authority, where people tend to follow the fatwas and views of the kiai rather than the provisions of state law, which has led to the prevalence of unregistered polygamy. In addition, the permission of the first wife in polygamy is an interesting issue, because positive law requires permission, while in fiqh there is no such provision. Therefore, it is important to increase public legal awareness regarding marriage registration and joint property agreements so that the rights of wives in polygamy can be protected more optimally.